Cacao surveys using free software Qfield and Android devices for the SENA project SGPS8548- CACAO - Ortíz Muñoz, Juan Carlos; Acevedo Gil, Carlos Mario; Velasquez Velez, Maria Isabel; Mejía Córdoba, Carlos Arturo (Revista Colombiana de Investigaciones Agroindustriales, 2021)
The objective of this work is to make known about the new technologies for capturing information in the field through a personalized design, guaranteeing uniformity and centralization of data to facilitate workflow, precision, data quality and help to improve research results. Geographical location and description of the object using an attribute form is a determining factor in field research. There are new technological tools that have the particularity of working without an Internet connection and can be installed on any Android computer. The selected study area corresponds to 5 subregions of the Department of Antioquia. On the other hand, cocoa is one of the main export products of the country, so its cultivation has increased in the last decade, however, there is no detailed census of these. The SENA learning service implemented through free software the capture of variables for cocoa crops in the project (SGPS8548- CACAO) using free software QGIS and the field information capture module QField. A total of 11 researchers captured field variables and the information was synchronized in the central database using the FolderSync application.